2018
DOI: 10.1002/lary.27357
|View full text |Cite
|
Sign up to set email alerts
|

Upper‐Airway Stimulation Before, After, or Without Uvulopalatopharyngoplasty: A Two‐Year Perspective

Abstract: Objective Upper airway stimulation (UAS) is an effective second‐line treatment for obstructive sleep apnea (OSA). In certain patients, there is a considerable need for advanced programming, notably with inadequate palatal response to therapy. The aim of the study was to investigate the impact of uvulopalatopharyngoplasty and tonsillectomy (UPPP‐TE) on UAS therapy outcomes from a 2‐year perspective after implantation. Methods This study included all consecutive patients implanted with UAS in which a full set of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…53,54 Another retrospective analysis found no indication for patients to routinely undergo UPPP before HNS, while palatal surgery could be suggested in case of non-adequate response to HNS after the implantation. 55 Accordingly, a recent study based on the Adhere Registry data (n = 299) showed that previous surgery is not associated with HNS outcomes. 52 In addition to previously described predictors, frequently used exclusion criteria are: more than 25% of central sleep apneas; positional OSA (>50% reduction in AHI between supine and non-supine positions); tonsil size greater than type 2; tongue malformations; alteration of tongue motor activity; marked salivation disorders; neuromuscular disease; hypoglossal-nerve palsy; active psychiatric disease; other non-respiratory sleep disorders; pregnancy; major systemic disorder; requirement of magnetic resonance imaging.…”
Section: Patient Selection and Efficacy Predictorsmentioning
confidence: 99%
“…53,54 Another retrospective analysis found no indication for patients to routinely undergo UPPP before HNS, while palatal surgery could be suggested in case of non-adequate response to HNS after the implantation. 55 Accordingly, a recent study based on the Adhere Registry data (n = 299) showed that previous surgery is not associated with HNS outcomes. 52 In addition to previously described predictors, frequently used exclusion criteria are: more than 25% of central sleep apneas; positional OSA (>50% reduction in AHI between supine and non-supine positions); tonsil size greater than type 2; tongue malformations; alteration of tongue motor activity; marked salivation disorders; neuromuscular disease; hypoglossal-nerve palsy; active psychiatric disease; other non-respiratory sleep disorders; pregnancy; major systemic disorder; requirement of magnetic resonance imaging.…”
Section: Patient Selection and Efficacy Predictorsmentioning
confidence: 99%
“…106 A combination of UPPP and hypoglossal nerve stimulation might also be beneficial. 107 Hypoglossal nerve stimulation has not been introduced in Sweden.…”
Section: Hypoglossal Nerve Stimulationmentioning
confidence: 99%
“…This includes encouragement for increased therapy usage or voltage, repeated HST or PSG, or DISE with stimulation 13 to optimize electrode configurations or identify persistent obstruction sites, such as the soft palate. 11 It is also our center's experience that recommending weight-loss programs is effective for overweight patients with persistent OSA problems. 4.…”
Section: Discussionmentioning
confidence: 99%
“…In some isolated cases, additional upper airway surgery was performed. [10][11][12][13] This study attempted to show that our center's approach of using HSTs for the initial sUAS evaluation would be similar to results using PSG titration at the M6, M12, or M24 evaluations.…”
Section: Introductionmentioning
confidence: 99%